PENGARUH MULTI FEEDSTOCK 1 BIODIESEL DAN MULTI FEEDSTOCK 2 BIODIESEL TERHADAP UNJUK KERJA FOUR STROKE DIESEL ENGINE MENGGUNAKAN VARIASI PISTON CHAMBER - Ahmad Rifqul Muzakki; Edi Haryono; Lely Pramesti (Proceedings Conference on Marine Engineering and its Application, 2023)
Petroleum fuel is one of the fuels that is always used in combustion motors, especially in dieselengines so that abiotic natural resources are limited. Petroleum makes natural resources depleted, whiletransportation facilities and industrial activities are declining. One of them, the use of diesel, which is an abioticnatural resource that continuously in the transportation sector will one day run out, so the thing that needs to beconsidered is the alternative fuel that can be made, namely biodiesel. Biodiesel is a renewable fuel and is generallymade from biological sources (vegetable and animal) and is environmentally friendly. Raw materials from biodieselthat can be used are palm oil, olive oil, canola oil, hazelnut oil, and castor seed oil. In this research I will classify theseraw materials into 2 compositions of multi-feedstock.biodiesel. The first is Multi-feedstock 1 biodiesel contained frompalm oil, olive oil and canola oil. Meanwhile, Multi-Feedstock 2 biodiesel contains palm oil, hazelnut oil, and castorseed oil. The two Multi-feedstock compositions will then be mixed with HSD (Pertamina Dex) so that they become B20,B35, and B100 fuel which will then be tested on Four Stroke Diesel Engines with different piston variations. Whichlater in this study will test with a flat piston chamber then continue using the LSCS piston chamber. For lamp loading,it uses 1000 watt and also data capture using engine rotation variations of 900 rpm, 950 rpm, 1000 rpm, and 1050rpm.